Passion or penalty eaudiobook - Brunner, Leah (D.C. Eagles Hockey, 2023)
Once, I knew this girl who sent a video of herself to her brother's best friend...while she was hopped up on pain meds. And he didn't reciprocate her feelings. Sounds like a hilarious story, right? WRONG. This really happened...to ME, Melanie Taylor. That was five years ago, so I'm over it—over him. At least, I thought I was...until West got traded to the D.C. Eagles and moved to the same city as me! Oh yeah, did I forget to mention my brother's best friend is Weston Kershaw? An incredibly talented and famous professional hockey player? Of course, I set out to avoid him completely but end up going to one of his games—against my will, I might add. When I have to face him again all of those stupid butterflies in my stomach return full force. Except this time, the attraction doesn't feel so one-sided. This is a closed-door, dual POV romcom with mild language and innuendo. Trigger warnings: childhood trauma/anxiety.